Sars-CoV-2 in the second half of pregnancy: Maternal and perinatal outcomes - Muñoz Taya, Rossana (2020)
Introduction: The COVID-19 pandemic is a global health and social emergency. Knowledge is still limited about its effect on pregnant women. Objective: To describe maternal-perinatal outcomes of COVID-19 according to severity classification in women hospitalized in the second half of pregnancy. Methods: Retrospective, descriptive, observational study from March to July 2020 at Edgardo Rebagliati Martins National Hospital. All hospitalized pregnant women with RT-PCR and/ or rapid positive test for SARS-CoV-2 were included. Pregnancies less than 20 weeks and epidemiological discharges were excluded. Maternal characteristics at admission and maternal-perinatal outcomes were grouped according to the clinical classification of the disease. The qualitative variables are presented in counts and percentages; and quantitative ones, in medians and ranges. Results: 247 pregnant women were studied. Most of them were in the third trimester (76%). The most frequent presentation of the disease was asymptomatic (83%), and cases of severe pneumonia were few (3.2%). The cesarean section rate was high (60%), although vaginal deliveries doubled over time (0-24 a 44%). Severe cases had a higher rate of cesarean section (100%) and iatrogenic preterm delivery (75%). No maternal deaths were reported. There were 9 stillbirths and 5 positive neonates for SARS-CoV-2, both among asymptomatic and mild patients. 9 stillbirths and 5 positive neonates for SARS-CoV-2, both among asymptomatic and mild cases. Conclusions: The possibility of cesarean section and iatrogenic preterm delivery is greater in severe cases. The vaginal delivery rate increased in recent months. No perinatal complications related to COVID-19 were identified.